Evoking Timelessness through Integration between Old and New Building - Mohammad Irfan Andhikaputra; Vincentius Totok Noerwasito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2017)
Architecture is inevitably influenced by time. One of the possible way to witness the influence of time in architecture is looking through the present old-structure building. The building that holds historical value to its society, are able to be used over time while retaining its form but adaptively reused by society to fulfill their needs. In the other hand, some buildings are just left abandoned by its society, although it may have the same value with the other “timeless” building. As to retain its historical identity, the government has issued some projects to rejuvenate this sector of Kota Tua. Selected site is developed and adapted, given its newest function as a museum by using pattern language and adaptive reuse as a method to achieve a suitable look of a timeless concept. The implementation of Timelessness into selected site is the main idea of this project, by placing the new structure adaptively through existing building, the integration of the old and new structure is achieved.